GENDER AND ONLINE DISCOURSE IN THE PRINCIPLES OF ECONOMICS - Graddy, Duane B. (Online Learning, 2004)
Collaboration is the heart of online learning. Interaction among course participants brings excitement to the online environment and creates knowledge as a group activity. Impediments to active collaboration reduce group, as well as individual, potentialities. Past studies of online discussions have found differences in the style of female and male conversations that could impede the learning process. The conversational styles of female and male students in two online principles of economics classes were analyzed in the present study. The null hypothesis posited no difference in the styles of online discourse between female and male students. The null hypothesis was rejected, implying gender differences in conversational styles. The tone of male postings was more optimistic than the tone of female postings. Female conversations used words revealing social isolation and the rejection of social norms. The paper also discussed the issue of the male X-factor in the principles of economics from a sociolinguistic perspective.